2013
DOI: 10.1099/mic.0.068676-0
|View full text |Cite
|
Sign up to set email alerts
|

A new subgroup of the IS3 family and properties of its representative member ISPpy1

Abstract: Institute of Molecular Genetics, Russian Academy of Sciences, Kurchatov sq. 2, Moscow 123182, RussiaRecently, we described a novel insertion element, ISPpy1, isolated from a permafrost strain of Psychrobacter maritimus. In this work, we demonstrated that ISPpy1 is a member of a novel subgroup of the IS3 family of insertion sequences (ISs) that was not identified and characterized previously. IS elements of this subgroup termed the ISPpy1 subgroup are broadly distributed among different taxa of Eubacteria, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The accessory region of the pKLH80 plasmid contains five antibiotic resistance genes: previously characterized genes, strA–strB and tetR–tet (H) (Petrova et al , 2009), and an additional gene discovered in this work, bla RTG . Two IS elements, IS Aba14 and IS Psma1 , were also found in this region, in addition to IS Ppy1 identified previously (Petrova et al , 2009, 2013).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The accessory region of the pKLH80 plasmid contains five antibiotic resistance genes: previously characterized genes, strA–strB and tetR–tet (H) (Petrova et al , 2009), and an additional gene discovered in this work, bla RTG . Two IS elements, IS Aba14 and IS Psma1 , were also found in this region, in addition to IS Ppy1 identified previously (Petrova et al , 2009, 2013).…”
Section: Resultssupporting
confidence: 72%
“…It should be noted that in contrast to IS Psma1 , only one copy of each of the two other mobile elements, IS Aba14 () and IS Ppy1 (Petrova et al , 2013), is present in the MR29-12 genome.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an additional subgroup has been proposed, which includes ISPpy1 (146). However, all members belong to the IS150 subgroup and their Tpases are not separated by our standard multiple alignment and Markov Cluster Analysis (MCL) analysis.…”
Section: (Ii) Organizationmentioning
confidence: 99%
“…1 d). An insertion sequence IS Ppy1 has similar sequence features with IS 1447 in terms of IRs [ 37 ], but its evolutionary relationship is not close to IS 1447 (see below). This indicated that IS 1447 may represent a novel IS 3 -family subgroup that has a diverse phylogenetic relation with known subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the Firmicutes branch, the non-Firmicutes branch showed low bootstrap values, indicating low confidence and high variability of the evolutionary relationships [ 38 ] (Additional file 1 : Figure S1). In addition, nucleotide sequence analysis showed that a large proportion (76.5%, 26 of 34 randomly selected sequences) of the insertion sequences from the non-Firmicutes branch exhibited no or − 1 frameshifting for the expression of Tpases, including the IS Ppy1 element from the plasmid pKLH80 of Psychrobacter maritimus MR29-12 (GenBank Accession Number AM992204), which was determined previously to display a subgroup of the IS 3 -family [ 37 ] (Additional file 1 : Figure S1). Thus, IS 1447 -like elements are primarily present in the phylum Firmicutes and not closely related to those from non-Firmicutes species.…”
Section: Resultsmentioning
confidence: 99%